PURCHASE INTENTION: STRONG EFFECTS OF GREEN ADVERTISING ATTRIBUTES, PARA-SOCIAL RELATIONSHIPS, AND PERCEIVED CREDIBILITY - Ifatuna Hasanah; Widiya Dewi Anjaningrum (Distribusi - Journal of Management and Business, 2023)
The issue of environmental pollution in recent years has become a global problem topic. The biggest trigger in Indonesia is plastic waste from daily activities, especially consumption patterns. The implementation of green marketing has begun to be carried out by every business actor as a form of participation in preventing environmental problems, as well as to educate consumers about the impacts. This study aims to determine the relationship between the green advertising attributes, para-social relationship, perceived credibility, and consumer purchase intentions for Starbucks products. Data collection on 270 samples of Starbucks consumers at Malang town was carried out by non-probability sampling through a questionnaire instrument. The data obtained were analyzed using Partial-Least-Square (PLS) analysis. The results showed that each of the green advertising attributes, para-social relationship, and perceived credibility had a strong positive effect on purchase intention. It is proven that there is a mediating role of perceived credibility on the effect of the para-social relationships on purchase intention. The love for green advertisements and the tendency to observe what influencers buy and use greatly influences consumers' buying interest and they feel that using environmentally friendly products will reduce guilt for environmental damage.